PEMBUATAN KERTAS RAMAH LINGKUNGAN KOMBINASI LIMBAH AMPAS TAHU DAN LIMBAH KULIT PISANG KEPOK DENGAN METODE PEMISAHAN ALKALISASI - Eka Margaret Sinaga; Supartiningsih Supartiningsih; Elly Sitorus; Sriadiprastio Sriadiprastio (Jurnal Farmanesia, 2019)
Tofu dregs waste contains 30.4% cellulose content, while kepok banana peel has high cellulose content (60-65%), hemicellulose 6-8%, and lignin 5-10%. The purpose of this study was to determine the process of making natural paper from tofu dregs waste and kepok banana peel waste as an alternative raw material for wood substitutes and to find out the characteristics of natural paper produced from tofu waste fiber and kepok banana peel waste based on SNI 287:2010 (including test water content) and SNI 6588-1:2010 (including pH acidity test). Based on the results of research that has been carried out, the optimum composition in making paper from tofu dregs and kepok banana peels is 50:50% variation. The temperature and time of heating and the optimum concentration of sodium hydroxide solution was 120 oC for 90 minutes with sodium hydroxide solution concentration of 10.0%, pulp content of 46.45%, cellulose content of 53.3%, and lignin content of 46.67%. All levels obtained have met the requirements of SNI. Based on the FT-IR spectrum analysis, tofu dregs and kepok banana peels are suitable for use as raw materials for making paper because they contain cellulose. Based on the SEM analysis, the morphological surface structure, the tighter the fiber bonds, this proves that the diameter of the resulting fiber is very small, because the smaller the fiber diameter, the better the mechanical properties.